Hubungan Paritas dengan Kejadian Rupture Perineum pada Persalinan Normal: The Relationship of Parity with the Occurrence of Perineal Rupture in Normal Delivery - Subriah, Subriah; Agustina, Ayu; Puspita, Erika Wanda; Rahmawati, Novi; Nurfatimah, Nurfatimah (Jurnal Bidan Cerdas, 2021)
Introduction: Even though labor was going normally, after giving birth the mother had various risks of complications that might occur, such as bleeding due to uterine atony, retained placenta, and perineal ruptur. Objective: to see the relationship between parity and the incidence of perineal ruptur in normal delivery. Methods: this type of research uses an analytical method based on a cross sectional design. The population is all mothers who give birth at the Kassi Kassi Health Center Makassar City can use 30 people. The sampling technique used was Consecutive Sampling. Results: The results showed 76.7% of respondents experienced perineal tears, of which 26.7% of respondents experienced 1st degree perineal tears and 50.0% of respondents had grade 2 perineal tears. 23.3% of respondents did not experience perineal tears. From the results of the chi-square test with a value of p=0.05, the probability of the result is greater than a significant tarf of 5% (0.071> 0.05), meaning that there is no parity relationship with perineal tears in mothers with normal delivery at the Kassi-Kassi Community Health Center, Makassar City. 2020. The strength of the relationship between variables is rather low, the value of the Phi coefficient (Î¼) = 0.488 or 48.8%. Conclusion: Based on the results of the research that has been done, it can be denied that there is no relationship between parity and perineal tearing in normal delivery.